The Netter collection of medical illustrations : Musculoskeletal System. Part III, Biology and Systemic Diseases - Iannoti, Joseph P.; Parker, Richard D.; Abelson, Abby G.; Patterson, Brendan M.; Machado, Carlos A. G.; Netter, Frank Henry, 1906-1991 (Cleveland Clinic, 2025)
The book provides a highly visual guide to embryology and physiology, metabolic disorders, congenital and development disorders, rheumatic diseases, tumors of the musculoskeletal system, injury to the musculoskeletal system, soft tissue infections, and fracture complications. Provides a concise overview of complex information by seamlessly integrating anatomical and physiological concepts using practical clinical scenarios. Shares the experience and knowledge of Drs. Joseph P. Iannotti, Richard D. Parker, Abby G. Abelson, and Brendan M. Patterson, and esteemed colleagues from the Cleveland Clinic, who clarify and expand on the illustrated concepts. Compiles Dr. Frank H. Netter’s master medical artistry―an aesthetic tribute and source of inspiration for medical professionals for over half a century―along with new art in the Netter tradition for each of the major body systems, making this volume a powerful and memorable tool for building foundational knowledge and educating patients or staff. An eBook version is included with purchase. The eBook allows you to access all of the text, figures, and references, with the ability to search, make notes and highlights, and have content read aloud.